Variable preservation of the 1991 Hudson tephra in small lakes and on land - Streeter, Richard T.; Cutler, Nick A.; Lawson, Ian T.; Hutchison, William; Dominguez, Lucia; Hiles, William (Frontiers in Earth Science, 2024)
Volcanic ash (tephra) preserved in terrestrial environments and lake sediments contains information about volcanic processes and can be used to infer eruptive parameters and frequency of past eruptions, contributing to the understanding of volcanic hazards. However, tephra deposits can undergo transformation from their initial fallout sedimentation to being preserved as a tephra layer in the sedimentary record. The process is likely to be different in lakes and in terrestrial (soil) sequences. Here we compare the thickness, mass loading and grain size of tephra layers from the 1991 eruption of Cerro Hudson, Chile, from small lakes and adjacent terrestrial settings to measurements of the tephra made shortly after the eruption. We analysed samples from 35 cores in total from six small lakes (<0.25 km2), located 76 and 109 km from the volcano in two contrasting climatic areas (cool and humid northern site, and warm and dry southern site), and made 73 measurements of tephra thickness and 11 measurements of grain size in adjacent terrestrial areas. The major element geochemistry of our samples confirmed they were from the 1991 Hudson eruption. We found that some of the measured characteristics of the preserved tephra layers were comparable to those recorded in 1991 shortly after initial deposition, but that there was considerable variability within and between locations. This variability was not predictable and lake sediments did not preserve a notably more accurate record of the fallout than terrestrial sites. However, in aggregate the characteristics of the preserved tephra was similar to those recorded at the time of deposition, suggesting that, for palaeotephra research, a sampling strategy involving a wide range of environments is more robust than one that relies on a single sedimentary record or a single type of sedimentary environment.